How integrated are the African stock exchanges?: evidence from long term comovement, returns and volatility spillovers - Kambadza, Tinashe Harry Dumile (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2011)
Stock market linkages have implications for portfolio diversification, asset pricing, monetary and regulatory policy as well as financial stability. This study examines the extent to which African stock markets are linked using daily data for the period 2000-2010. The study is divided into three main parts each focussing on the ways in which integration of the stock markets can be viewed. Firstly, we analyse the long run co-movement of the stock markets using both bivariate and multivariate Johansen (1988) and Johansen and Juselius (1990) cointegration approaches. Secondly, we analyse returns linkages using Factor analysis and the Vector Autoregressive (VAR) models. In the Factor Analysis model, we used two extraction methods, namely Principal Component Analysis and the Maximurn Likelihood technique. The VAR model was extended with impulse response, variance decomposition and block exogeniety. Thirdly, we analyse the behaviour of volatility and the volatility linkages among the stock markets. We initially analysed and modelled volatility in each stock market using the GARCH, EGARCH and GJR GARCH and then examined the long-term trend of the volatility. Conditional volatility series for each country were then estimated using the most appropriate model and were analysed using VAR, block exogeniety, impulse response and variance decomposition to determine the extent of their linkages. The findings of the study are as follows: Both the bivariate and multivariate models found slim evidence of cointegration amongst the stock markets, suggesting that there were opportunities for portfolio diversification for investors. In general, the financial crisis had very little impact on the long-run relationships of the stock markets. Results for the returns linkages showed that there were limited retums linkages with the exceptions of South African-Namibia and Egypt-Morocco to a lesser extent. South Africa was found to be the most endogenous, whilst Ghana and Nigeria were the most exogenous on the continent. We regards to volatility, we found that it was asymmetric and persistent across all the stock markets with long term trend of volatility showing that it significantly increased for most of the markets. Finally, there were limited volatility linkages, only between South Africa, Egypt and Namibia, implying that African stock markets are still largely segmented from each other. However, the linkages between South Africa and Egypt could have negative effects as they could lead to the spread of contagion effects during times of crises. Therefore, policymakers should consider revising and improving policies to enhance economic integration on the continent.
Keywords: Stock exchanges -- Africa; Money market -- Africa; Globalization -- Economic aspects -- Africa; International economic relations